The content of interleukin-6 in the oral fluids of patients with multiple myeloma - G F Sakhapova; L P Gerasimova; M F Kabirova; I N Usmanova; L M Masyagutova; I D Rybakov (RUDN Journal of Medicine, 2009)
Complex dental examination of patients with multiple myeloma has been done. Eighteen subjects with immunoglobulin A (IgA) secretion and 30 subjects with Ig G secretion were entered into the study. We have studied IL-6 content indicators in the oral fluids and blood serum. The dependence of interleukin-6 (IL-6) indicators on duration of the underlying disease, and conducted chemotherapy has been detected.